Collision-kerma conversion between dose-to-tissue and dose-to-water by photon energy-fluence corrections in low-energy brachytherapy. (16th December 2016) - Giménez-Alventosa, Vicent; Antunes, Paula C G; Vijande, Javier; Ballester, Facundo; Pérez-Calatayud, José; Andreo, Pedro
Abstract: The AAPM TG-43 brachytherapy dosimetry formalism, introduced in 1995, has become a standard for brachytherapy dosimetry worldwide; it implicitly assumes that charged-particle equilibrium (CPE) exists for the determination of absorbed dose to water at different locations, except in the vicinity of the source capsule. Subsequent dosimetry developments, based on Monte Carlo calculations or analytical solutions of transport equations, do not rely on the CPE assumption and determine directly the dose to different tissues. At the time of relating dose to tissue and dose to water, or vice versa, it is usually assumed that the photon fluence in water and in tissues are practically identical, so that the absorbed dose in the two media can be related by their ratio of mass energy-absorption coefficients. In this work, an efficient way to correlate absorbed dose to water and absorbed dose to tissue in brachytherapy calculations at clinically relevant distances for low-energy photon emitting seeds is proposed. A correction is introduced that is based on the ratio of the water-to-tissue photon energy-fluences. State-of-the art Monte Carlo calculations are used to score photon fluence differential in energy in water and in various human tissues (muscle, adipose and bone), which in all cases include a realistic modelling of low-energy brachytherapy sources in order to benchmark the formalism proposed. The energy-fluence based corrections given in this work are able to correlate absorbed dose to tissue and absorbed dose to water with an accuracy better than 0.5% in the most critical cases (e.g. bone tissue).